THE EFFECT OF SERVICE QUALITY, BRAND IMAGE, AND PRICE ON CUSTOMER SATISFACTION AT CV. MEDAN BAROKAH - Dewi Wahyuni Friend Siska Pinem; Ade Rahma Ayu (SEAN Institute, 2023)
The purpose of this study was to determine whether there is an effect of service quality, brand image and cost on customer satisfaction at CV. Medan Barokah. The pattern in this observation is 60 buyers at CV. Medan Barokah, sampling using a non probability sampling approach with incidental sampling. fact analysis using linear regression test more than one, speculation test using determination coefficient test (R²), partial test (t test), and simultaneous test (F test), and statistical processing using SPSS 22. The results showed that good service, brand image and cost have been able to provide an explanation during his life to the variable buyer satisfaction to shop again, except that partially good service, brand image and cost have a tremendous impact on customer satisfaction. simultaneously good service, brand image and cost have a tremendous and tremendous impact on buyer choice.